2018
DOI: 10.5812/asjsm.57500
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rest Interval Length Between Sets on Total Load Lifted and Blood Lactate Response During Total-Body Resistance Exercise Session

Abstract: Objectives: This study aimed to investigate the effect of different rest interval durations between sets during full-body resistance exercise sessions on total load lifted and blood lactate concentrations in resistance-trained individuals.Methods: Ten healthy young men (age: 23 ± 6.5 years; total body mass: 82.8 ± 10.6 kg, height: 177.3 ± 0.1 cm) randomly performed 3 resistance exercise sessions with different rest intervals between sets (30 seconds, 60 seconds and 120 seconds). The resistance exercise session… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Tredrea 33 , based on a literature review, found that in intense strength training (> 80% of 1RM), only intervals of 4–8 min allowed the next set of plyometric exercises to be performed at a similar power level. Furthermore, Lopes et al 34 showed that doubling the duration of the interval between sets (from 30 to 60 s) allowed participants to perform significantly more repetitions in a set but increasing the interval from 60 to 120 s no longer increased the number of repetitions.…”
Section: Discussionmentioning
confidence: 99%
“…Tredrea 33 , based on a literature review, found that in intense strength training (> 80% of 1RM), only intervals of 4–8 min allowed the next set of plyometric exercises to be performed at a similar power level. Furthermore, Lopes et al 34 showed that doubling the duration of the interval between sets (from 30 to 60 s) allowed participants to perform significantly more repetitions in a set but increasing the interval from 60 to 120 s no longer increased the number of repetitions.…”
Section: Discussionmentioning
confidence: 99%
“…Lactate, an anaerobic by-product that is formed when pyruvate binds to two hydrogen ions after glycolysis [92,96], is often used as a proxy measure of metabolic stress during various styles of RT [89,90]. Rogatzki et al [67] demonstrated that endurance-style RT (2 sets, 20 reps, 50 % of 1-RM) elicited greater blood lactate response than hypertrophy (3 sets, 10 reps, 70 % of 1-RM) and strength (5 sets, 5 reps, 85 % of 1-RM) RT during back squat exercise.…”
Section: Acute Metabolic Effects Of High-volume Low-intensity Rtmentioning
confidence: 99%